Advanced Care Planning for Patients with End Stage Renal Disease: An Integrative Review - Acharya, Devaka Kumari; Nilmanat, Kittikorn; Boonyasopun, Umaporn (Journal of Nursing Education of Nepal, 2022)
Introduction: Patients with end stage renal disease have a high rate burden of disease and mortality. Advance care planning is important for improving the end-of life care for these patients but it is complex and challenging. This review aims to find out the interventions, context and experiences of advance care planning for end stage renal disease.Methods: Databases ProQuest Nursing and Allied Health, Cumulative Index to Nursing and Allied Health Literature, Google Scholar, PubMed were searched for 15 years’ period from 2006-2020 yielded 10 articles. We included the studies with adult patients, diagnosed with end stage renal disease, have hemodialysis, peritoneal dialysis or without dialysis, any setting and any design quantitative and qualitative, any interventions and outcomes, qualitative studies, and family members and significant caregivers.Results : We included ten studies that involved 1526 participants (one study not mentioned theparticipants) which investigated advance care planning to patients with end-stage renal disease and their families/friends/surrogates. The interventions used were Patient‐centered Advance Care Planning, Peer-mentoring, Printed material, Booklets and patient expert, Sharing Patient’s Illness Representations to Increase Trust, Model test. Patients and caregivers felt the more need of advance care planning.Conclusion: Advance care planning needs to include as important component of renal care formanagement of patients with end stage renal disease though it is inadequately used. More interventional studies are needed to be carried out to find the most effective intervention and context to manage this trajectory illness.
Keywords: Advance care planning; advanced directive; ESRD; hemodialysis; interventions